Effect of trisodium citrate mastitis treatment on some milk constituents in cows - SINGH, (The Late) T J; VARINDRA, VARINDRA; SINGH, SUDARSHAN; DHILLON, K S (The Indian Journal of Animal Sciences, 2013)
Study was conducted on 10 crossbred cows suffering from mastitis. Mastitic milk consistency was abnormal bnormal with high pH and low percentage of citrate. total proteins, lactose and fat, compared to normal milk, Following .treatment with trisodium citrate. milk consistency, pH and percentage of above constituents was restored to near normalcy.